2006
DOI: 10.1136/adc.2004.061416
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental perceptions of diabetes and glycaemic control

Abstract: Parents' perceptions of their children's diabetes are significantly related to glycaemic control; however, those who appear more competent at managing diabetes may overestimate their child's capabilities, leading to poorer glycaemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…(2003) found that children maintaining good control were more likely to manage their care independently than children maintaining poor control. By contrast, Pattison et al. (2006) revealed that children perceived by their parents as displaying greater competence in managing their diabetes had poorer actual control.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…(2003) found that children maintaining good control were more likely to manage their care independently than children maintaining poor control. By contrast, Pattison et al. (2006) revealed that children perceived by their parents as displaying greater competence in managing their diabetes had poorer actual control.…”
Section: Resultsmentioning
confidence: 86%
“…Nabors et al (2003) found that children maintaining good control were more likely to manage their care independently than children maintaining poor control. By contrast, Pattison et al (2006) revealed that children perceived by their parents as displaying greater competence in managing their diabetes had poorer actual control. Higher blood glucose level variability and more severe hypoglycaemia were negatively related to the ability to estimate blood sugar level correctly (Gonder-Frederick et al 2008).…”
Section: Illness and Carementioning
confidence: 86%
“…Parents struggle with their child's usual as well as specific developmental needs. According to Robinson (1993), this can often result in a trade off; whilst 'good' glycaemic control may be a primary aim for both parents and children, this can be traded off to allow the family to feel they live a normal life (Pattison et al 2006). Children have to accept more responsibility (such as refusing sweets and being careful) than their peers and have to accommodate an individual diabetic notion of 'normal' into their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that maternal self-efficacy is positively associated with better diabetes self-management in their children (Leonard, Skay, & Rheinberger, 1998), others have not found any significant associations (Marvicsin, 2008). Pattison, Moledina, and Barrett (2006) found that although parental self-efficacy did not predict glycemic control in children with Downloaded by [Dalhousie University] at 20:33 05 October 2014 T1D, it was associated with greater normalization (minimizing feelings of the child with diabetes and family as being different).…”
mentioning
confidence: 99%